Mulheres sindicalistas: estudo da análise discursiva do Sindicato dos Servidores Públicos do Ceará. - Alves, Karla Suleny Bessa da Silva (2024)
In Brazilian unionism, over the decades, the dominant ideology has conditioned the (non)participation of women in decision-making spaces, even promoting the erasure of our contributions and protagonism in the history of the union struggle and the labor world. Our main research question is: what prominent positions do women occupy in the Municipal Public Servants' Unions of Ceará? In view of this, the objective of this study is to investigate which prominent positions women have occupied in the Municipal Public Servants' Unions of Ceará, outlining and identifying the history of participation and the evolution of the presence of women in Ceará unionism, understanding the importance of this presence from the standpoint of the women participating in these unions. The research will be of a documentary and bibliographic nature with a qualitative approach, carrying out a literature review on discussions about gender and the presence of women in unionism in Brazil, with a focus on Ceará, as well as women from the regional unions of municipal public servants in the state of Ceará. The entire theoretical-methodological process will take place in the light of Pêcheux's Discourse Analysis, in which discourse (the production of meanings between interlocutors) is the link between language and history and the subject (of discourse) is interpellated by ideology, constructing their subjectivation and their social projection. It is hoped to understand how gender has been historically discussed, including in studies on women, and how this is linked to the history of women in Brazilian unionism, especially in the unionism of the state of Ceará.